Measuring Recidivism Rate: Its Predictive Variables and Antecedents - Delfin, Maria Diana B.; Dalugdog, Wilfredo D.; Dausan, Alrien F.; Villa-Buena, Elizabeth S. (Future Science / FSH-PH Publications, 2023)
This study examined the recidivism rate at the Bureau of Jail Management and Penology – National Capital Region (BJMP-NCR), Philippines, from 2020 to 2022 based on predictive variables and antecedents of recidivism. The results revealed that young individuals; males; married; Person Deprived of Liberty (PDL) with drug cases, leading to death or intending to cause death, and acts involving fraud and deception; and those having shorter stays in prison tend to recidivate more. Likewise, the pattern of recidivism in the Metro Manila District Jail (MMDJ) from 2020 to 2022 was affected by the existence of the COVID-19 pandemic. In conclusion, both predictive variables and antecedents of recidivism show no significant association with the pattern of recidivism.